Emon: an R‐package to support the design of marine ecological and environmental studies, surveys and monitoring programmes. Issue 10 (20th March 2017) - Barry, Jon; Maxwell, David; Jennings, Simon; Walker, David; Murray, Joanna
Summary: Marine systems and their biota are always changing, in response to environmental and human pressures such as climate variation and change, eutrophication, fisheries exploitation, litter, noise and accidental releases or regular discharges of contaminants, radioactivity and hazardous substances. Studies, surveys and monitoring help to describe and understand system responses to these pressures, and provide evidence to assess the needs for, and effects of, management interventions. Studies, surveys and monitoring are often costly, especially offshore, so small investments in preliminary data collection and systematic planning of these activities can help to make best use of resources and inform trade‐offs between budgets and expectations. To meet recognised needs for accessible tools to plan some aspects of studies, surveys and monitoring, we developed the R package emon . Emon includes routines for study design through power analysis (assuming independence of observations) and feature detection; which are the focus of this paper. We hope that access to the functions in emon, many drawing on work which was previously published but without code for implementation, will raise awareness of what marine studies, surveys and monitoring can achieve, thus encouraging cost‐effective, needs‐ and evidence‐based designs.